DETERMINANT EMPLOYEE TURNOVER INTENTION - Nazifah Husainah (Sosiohumaniora, 2023)
The purpose of this study is to find out and analyze the influence of leadership style on change intention, the influence of motivation on change intention, and the influence of recruitment process on PT change intention. Centana Group Inc. The research used in this study used a type of quantitative research. At the same time, the research method used in this study adopts association method. The data collection methods used in this study are literature research and field research. The sampling method used is non-probability sampling. Based on the results of this study, it is found that leadership style has no significant negative impact on turnover intention, motivation has a significant positive impact on turnover intention, and recruitment process has no significant negative impact on turnover intention. For this study, the authors made recommendations for different parties, including exogenous variables (leadership style, motivation, recruitment process). In this study, only 52.3% of the effect on the endogenous variable (sales intention) was explained, while 47.7% was influenced by other unexplored exogenous variables. This should enable future researchers to also use other exogenous variables such as organizational culture, compensation and career development